PENGARUH KEPEMIMPINAN INSTRUKSIONAL KEPALA SEKOLAH TERHADAP KINERJA MENGAJAR GURU SMK SE-KECAMATAN BOJONGLOA KIDUL KOTA BANDUNG (Jurnal Tata Kelola Pendidikan, 2019)
Research is called “The Influence of Principal Instructional Leadership to the TeachingPerformance of Vocational Secondary School Teacher at Bojongloa Kidul BandungCity.”This research using two variable, x variable is Principal Instructional Leadershipand y variable is Teaching Performance. The study is done in 6 Vocational Secondaryschools at Bojongloa Kidul Bandung with respondents research the school teacher ineach school. In general the purpose of this research was to give how much influence ofPrincipal Instructional Leadership to the Teaching Performance of VocationalSecondary School Teacher at Bojongloa Kidul Bandung City. The study is done by usingthe method descriptive and approach quantitative supported to the study literature.Technique data collection using a questionnaire, who became population is a teacher ofvocational secondary school at Bojongloa Kidul Bandung City with a sample of 70respondents. Analysis thinks in this study use some help program Microsoft Excel 2007and application spss 21.0 for windows. The calculation on Weight Means Score (WMS),shows that Principal Instructional Leadership Vocational Secondary School Teacher atBojongloa Kidul Bandung City be in the very high with an average all the aspects 4,38.For the performance of teachers to teach are in the high with an average all the aspects4,31. Based on the calculation t test obtained thitung = 20.58> ttabel = 1.668 means thatthere is a very significant influence between Instructional Leadership Principal TeacherTeaching Performance Against SMK Bojongloa District of Bandung Kidul, bycalculating the coefficient of determination stating their influence between the variablesof 84.64%.
Keywords: Principal Instructional Leadership and the performance of teachers